Impact of COVID-19 on Families of Pediatric Solid Organ Transplant Recipients. (27th July 2021) - Forner-Puntonet, Mireia; Castell-Panisello, Eudald; Quintero, Jesús; Ariceta, Gema; Gran, Ferran; Iglesias-Serrano, Ignacio; Gisbert-Gustemps, Laura; Daigre, Constanza; Ibañez-Jimenez, Pol; Delgado, Mercedes; Español-Martín, Gemma; Parramon, Gemma; et al.
Abstract: Objective: The COVID-19 pandemic and lockdown measures have had a clear psychological impact on families, and specifically those with children with chronic illnesses have reported greater overloads and exhaustion. The objective of this study was to evaluate the exposure, impact and experience of the pandemic on families of pediatric solid organ transplant (SOT) recipients compared to families of healthy children and adolescents. Methods: We recruited 96 families, 48 with a pediatric SOT recipient and 48 healthy controls, matched by child age and gender. A primary caregiver from each family responded to an online sociodemographic questionnaire and the COVID-19 Exposure and Family Impact Survey (CEFIS), which explores the exposure, impact and experience of the pandemic and lockdown on families. Results: Exposure to the pandemic was greater in families of healthy children and adolescents. The impact was mostly negative in both groups: caregivers reported increased anxiety (76%) and mood disturbances (71.9%) and hindered quality of sleep (64.6%) and health habits (58.3%). On the positive side, family relationships improved. Qualitatively, the SOT group positively perceived isolation and established hygienic measures as protective and destigmatizing, although they reported fear of virus transmission to their child. Conclusions: The psychological impact of the pandemic has been similar in both groups, although families of transplant recipients have protected themselves more, probably because they are used to prevention measures and they see contagion as a graver risk. Additionally, SOT recipients' families presented some idiosyncratic elements, especially a decrease in their perception of stigma associated with the medical condition.